Comparison of clinical and economic outcomes between the direct anterior approach and the posterolateral approach for primary total hip arthroplasty - Paweł Skowronek; Michał Dębiński; Agnieszka Maksymiuk-Kłos; Andrzej Zalewski; Robert Jopowicz; Tomasz Sasinowski; Arkadiusz Madej (Archives of Medical Science)
Introduction Total hip arthroplasty (THA) is one of the most frequently performed surgical procedures in orthopedics. The most commonly employed approaches are the posterolateral approach (PLA) and the lateral approach. Minimally invasive techniques such as direct anterior approach (DAA) and minimal invasive surgery direct anterior approach (MIS DAA) are used more and more often. The aim of the study was to compare the two approaches DAA and PLA in terms of length of stay, economic outcomes, quality of life, hip joint function and hip joint awareness.